HUBUNGAN RATING BINTANG TERHADAP PERAN AKUNTANSI MANAJEMEN STRATEGIS (Studi Empiris Pada Perusahaan Hotel di Sumatera Selatan) - Setiawan, Antonius Singgih; Rahmawati, Rahmawati (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to test whether the star rating as parameter of level hotel to bring a better impact on the implementation of strategic management accounting role in the management of the hotel business. Using a sample of 66 respondents General Manager/Leader of Hotel in the province of South Sumatra (resepon rate 88%), research hypotheses were tested using regression analysis. The results showed that the star rating hotel a positive impact on the implementation of strategic management accounting role in functional role of accounting and the use of strategic management accounting techniques.